Metabolic syndrome in first‐time hospitalized patients with depression: a 1‐year follow‐up study. (7th August 2015) - Nyboe, L.; Vestergaard, C. H.; Lund, H.; Møller, M. K.; Videbech, P.
Abstract : Objective: Studies on metabolic syndrome (MetS) in younger patients with depression are few. We examined the prevalence and progression of MetS in first‐time hospitalized patients with depression during 1 year of follow‐up. Furthermore, we explored putative risk factors of MetS. Method: We evaluated MetS and its components in first‐time hospitalized patients with depression ( N = 52) and healthy controls ( N = 50) (18–45 years). Physical activity, aerobic fitness, sleeping disturbances, smoking and dietary habits, and psychopharmacological treatment were recorded at baseline for all participants and after 1 year for the patients. Results: Patients had significantly higher waist circumference (WC) and lower high‐density lipoproteins compared with healthy controls ( P < 0.05). Patients had higher prevalence of MetS, but this was not significant when adjusted for age. Patients had significant increase in WC and triglycerides and a non‐significant increase in the prevalence of MetS. Antipsychotic medication (OR 10.5, 95% CI 1.18–94.14) and low aerobic fitness (OR 0.79, 95% CI 0.68–0.93) were significantly correlated with MetS ( P < 0.05). Conclusion: Metabolic syndrome is highly prevalent in younger, severely depressed patients and the incidence increases during 1 year of follow‐up. Low aerobic fitness and use of atypical antipsychotics are strongly correlated with MetS.